siklus Kontrak Bursa Komoditas Dalam Presfektif Hukum Ekonomi Islam - Efrinaldi Efrinaldi (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2016)
In futures trading the cycle of contract and types of transactions appear as a pure trade, which reduces the risk to make a profit from the difference between buy-sell, as a result of price fluctuations on the commodity being traded. Price fluctuations are predictable and the transaction begins with an analysis, while risk can be protected. Cycle contracts and the types of transactions in goods that are physical and on the spot market can be tolerated in Islamic economic law. The types of trade (al-tijarah) has been set in Personality ‘, because it forms the transaction on the spot market which has also been tolerated in the time of Prophet Muhammad. Spot market, such as transactions in agricultural products, livestock, minerals, handicrafts, industry, and others. While transactions in services that are non-physical, eg lease (al-Ijara) and wage-hired. While the trade object is basically objects that have economic value to the availability of goods during the transactions. In a review of Islam, this also applies to goods that are not available or without presenting the goods when the transaction, with the provision that ordered the concrete object properties. With concern to ba’i assalam or trading for non exist commodities, in the study of economic law of Islam, depending on the seller’s effective control and ability to deliver. Because no protection for the value of goods traded, and the protection of consumer interests from losses and no disappointments at a later date.